Irrigation Interval and Ethephon Regimes Shaping Alfalfa Yield and Quality - Sundus Kamel J Alhilfi; Fatimah Ali Jamel; Sabreen H. A. Al-Rubaiee (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Alfalfa (Medicago sativa L.) is a key perennial forage crop valued for high biomass and protein content, yet its productivity is strongly constrained by water scarcity and suboptimal canopy management, particularly in arid regions. Specific Background: In southern Iraq, reduced water availability from major rivers necessitates efficient irrigation scheduling alongside agronomic practices that regulate plant architecture. Knowledge Gap: Limited field-based evidence integrates irrigation intervals with ethephon application to clarify their combined role in determining forage yield and quality attributes of alfalfa. Aims: This study examined growth traits, green and dry forage yield, and protein characteristics of alfalfa under different irrigation intervals and ethephon spray concentrations. Results: An intermediate irrigation interval (10 days) combined with moderate ethephon concentration (0.5 ml L⁻¹) consistently produced the highest branch density, forage yields, protein percentage, and protein yield, with significant interaction effects across traits. Novelty: The study demonstrates a synergistic irrigation–ethephon management window that optimizes source–sink balance under water-limited conditions. Implications: These findings support adaptive irrigation scheduling coupled with growth regulator use to sustain forage productivity and quality in arid and semi-arid agroecosystems. Highlights: Optimal irrigation interval maximized alfalfa biomass and protein yield. Moderate ethephon concentration promoted branching and canopy efficiency. Combined management improved forage quality under water-limited conditions. Keywords: Alfalfa, Irrigation Interval, Ethephon, Forage Yield, Protein Quality